English reading habits of grade 10 students At high school of education sciences = Thói quen đọc tiếng Anh của học sinh lớp 10 tại trường THPT khoa học giáo dục - Nguyễn, Phương Anh (2020)
In this study, the researcher tried to display the very important roles of English reading habits in the development of reading skill for students. The results of the analysis have answered the research questions into five points: First, the results show the HES students’ current situation of English reading: they spend not much time for reading (about 1 hour per day for reading), they are taught and encouraged to learn to read books and materials while learning English at primary level, most students read less than 5 books per week, students spend less time on reading led to low writing skills, the purpose of reading English is for improving English skills and for improving knowledge. The results showed that planned students can schedule work for a week or a month, and they will also need to schedule study each week. Make a weekly to-do plan to find out when they can and need to complete your homework, enhance good reading habits quite soon. This way they will know the amount of time they need to set aside for each subject and the most appropriate time to study. Second, factors affecting HES students’ English reading are the support of teachers, internal motivation and support from their parents. Teachers who share a love of reading will help students establish English reading habits. When students have the internal motivation, they will have the power for studying and learning English. Besides, parents also play an important role to help students in the beginning step of the reading habit. Third, the study also offers some solutions to improve the habit of reading English in regard to students, teachers, parents and schools. Students need to be aware